Interpreting Community Narratives on the Value of Money and Exchange in Rural Digital Economies - Indah Elychia Samuel (International Publisher (YAPENBI), 2025)
This study explores how rural communities understand the value of money and exchange systems in the emerging digital economy. As digital financial services—such as mobile banking, QR-based transactions, and digital wallets—penetrate rural areas, traditional meanings of monetary value are being renegotiated. Using a narrative-based qualitative approach, data were collected from 24 participants in three rural areas of Indonesia through in-depth interviews and focus group discussions (FGDs). Thematic analysis identified four main themes: (1) money as a social value in local transactions, (2) coexistence of traditional and digital practices, (3) resistance to digitalization due to literacy gaps and trust issues, and (4) the rise of hybrid exchange models. Findings reveal that while digital tools provide speed and convenience, their abstract and impersonal nature often conflicts with traditional values of reciprocity, social trust, and tangible exchange. The study concludes that the value of money in rural digital economies is not only economic but also cultural and relational, reflecting a hybrid understanding in which digital and traditional logics converge. These insights highlight the importance of designing digital financial inclusion policies that are culturally sensitive and aligned with the social logic of rural communities.